Effects of a 12-week functional training program on the strength and power of Chinese adolescent tennis players - Xiao, Wensheng; Bai, Xiaorong; Geok, Soh Kim; Yu, Dawei; Zhang, Yang (Multidisciplinary Digital Publishing Institute, 2023)
Background: Functional training is any type of training designed to improve a specific movement or activity for fitness or high performance sports. This study examined the effect of functional training on the strength and power of young tennis players. Methods: 40 male tennis players were assigned to the functional training group (n = 20; age, 16.7 ± 0.4 years) or the conventional training group (n = 20; age, 16.5 ± 0.6 years). The functional training group received three 60 min sessions per week for 12 weeks, while the conventional training group participated in three sessions per week of mono-strength exercise for 12 weeks. Strength and power were measured according to the International Tennis Federation protocol at baseline, 6 weeks after the intervention, and 12 weeks after the intervention. Results: Both forms of training increased (p < 0.05) push-ups, wall squat test, over medicine ball throw, and standing long jump after 6 weeks of training, and the effect improved further as the 12-week mark approached. Except for the wall squat test (left) at 6 weeks, functional training showed no advantage over conventional training. After an additional 6 weeks of training, all measures of strength and power were better (p < 0.05) in the functional training group. Conclusions: Improvements in strength and power could occur after as little as 6 weeks of functional training, and 12-week functional training could outperform conventional training in male adolescent tennis players.